Digitalisasi Pemasaran dan Pemanfaatan Limbah Menjadi VCO - Fanggidae, Rolland E.; Molidya, Aldarine (Jurnal Abdimas Multidisiplin, 2023)
Purpose: The purpose of implementing this PkM is to provide education to the community to be able to manage coconuts in order to produce a product that has economic value, which is converted into Virgin Coconut Oil (VCO). Method: The method used is through training in the process of squeezing old coconut into raw material for VCO, providing counseling on the use of technology, procurement and supply of raw and auxiliary materials, layout and equipment, production supervision, production quality and packaging. Results: The result of the PkM carried out is that the community can produce their own VCO with the product name Alamanda VCO. Conclusions: The conclusion that can be drawn from this PkM is that there is an increasing understanding of the importance of online marketing. There are legal aspects that must be considered, especially those related to regulations and are regulated in the Electronic Information and Transaction Law (UU ITE) in online marketing. The determination of the price of Alamanda's VCO products is carried out through several considerations based on the results of the material exposure. 16 business actors already have accounts registered in the shopee market place. By holding a series of programs, partners are expected to increase profits and develop their business activities even better in the future. Limitations: limitations of researchers in conducting this research, namely limited funds. Contribution: This research can be useful in areas where there are many coconut trees, in economics and especially regarding the effective and efficient use of natural resources.